Mechanistic insights into the luminescent sensing of nitrophenol compounds by a cationic Zn-based metal-organic framework. (March 2022) - Liu, Yuhang; Wang, Yaohui; Zhang, Yi; Karmaker, Pran Gopal; Zhang, Lilei; Huo, Feng; Yang, Xiupei; Zhao, Bin
Abstract: Nitroaromatic compounds (NACs) are considered as a kind of toxic chemicals that pose a serious danger to the survival of animals and humans. Therefore, it is of great significance to develop an efficient and rapid method for detecting nitroaromatic explosives. Up to now, fluorescence metal-organic framework (MOF) has been widely used to detect NACs in environmental pollutants because of their many active sites and bare functional groups. In this work, we have synthesized a cationic Zn-based MOF (called F1 ) based on bis-(imidazole) ligands with the formula of [Zn3 (TIAB)2 (IMDC)2 ]·(NO3 )2 ·(DMF)2 ·(H2 O)2 (TIAB = [(1, 2, 4, 5-tetra(1H-imidazole-1-yl)benzene)], IMDC = 4, 5-imidazoledicarboxylic acid, DMF = N, N-Dimethylformamide). Crystal structure analysis reveals that F1 possesses a three-dimensional (3D) framework with (4, 8)-coordinated network. TIAB linkers connect the Zn(II) atoms to construct a 2D network, the deprotonation of the hydroxyl groups on the two carboxyl groups of the IMDC ligand, and the protonated IMDC 2− dangling fills the channel connected to two Zn1 atoms and one Zn2 atom, which are further connected TIAB ligands to form a 3D cationic framework. The results reveal that, compared with nitro aliphatic and aromatic compounds, the solvent-free F1 is highly sensitive and has excellent selectivity for nitroaromatic explosives, especially for 2, 4, 6-trinitrophenol (TNP). The quenching efficiency of TNP is as high as 91.67% ( K sv = 56760 M −1, LOD = 0.78 μM). The solvent-free F1 can be reused at least five times, and the response time to TNP is less than 30 s. The sensing and detection mechanisms of the solvent-free F1 to various NACs have been studied in detail. Finally, the response of solvent-free F1 to a variety of NACs was analyzed by density functional theory. Graphical abstract: Image 1 Highlights: A cationic Zn-based MOF shows good selectivity and sensitivity to nitroaromatic compounds. Distinguish between nitroaromatic and nitro aliphatic compounds. F1 can quickly detect TNP within 30 s and cycle five times to maintain the stability of the structure. Reveal a variety of detection mechanisms through experiments and theoretical calculations.